2010
DOI: 10.1186/1476-9255-7-19
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation in túbulo-interstitial damage associated to obstructive nephropathy

Abstract: Obstructive nephropathy is characterized by an inflammatory state in the kidney, that is promoted by cytokines and growth factors produced by damaged tubular cells, infiltrated macrophages and accumulated myofibroblasts. This inflammatory state contributes to tubular atrophy and interstitial fibrosis characteristic of obstructive nephropathy. Accumulation of leukocytes, especially macrophages and T lymphocytes, in the renal interstitium is strongly associated to the progression of renal injury. Proinflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
119
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 139 publications
(185 reference statements)
3
119
0
7
Order By: Relevance
“…In obstructed kidneys, Ang II levels have been proven to be markedly elevated [10,11] , whereas Ang II type 1 receptor blocker (ARB) and angiotensin-converting enzyme inhibitor (ACEI) demonstrate significant antifibrotic effects [15,17] . Furthermore, the formation of renal cortical TGF-β1 and related fibrogenic factors can be considerably reduced by angiotensinogen antisense RNA treatment in early UUO [16] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In obstructed kidneys, Ang II levels have been proven to be markedly elevated [10,11] , whereas Ang II type 1 receptor blocker (ARB) and angiotensin-converting enzyme inhibitor (ACEI) demonstrate significant antifibrotic effects [15,17] . Furthermore, the formation of renal cortical TGF-β1 and related fibrogenic factors can be considerably reduced by angiotensinogen antisense RNA treatment in early UUO [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of renal interstitial fibrosis is unclear, increasing evidence suggests that the excessive activation of the local renin-angiotensin system (RAS), which leads to a prominent elevation of angiotensin II (Ang II), is involved in the progression of CKD [10][11][12] . Previous in vivo studies have shown that the elevation of Ang II by chronic infusion results in renal fibrosis, which is associated with expression of proinflammatory cytokines and fibrosis-associated genes [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, obstructive nephropathy leads to activation of the intrarenal RAS, 13 and Ang II has a central role in the initiation and progression of obstructive nephropathy, by stimulating the production of molecules that contribute to renal injury (such as NF-kB activation and the subsequent increased expression of proinflammatory genes). ACE inhibitors reduce monocyte/ macrophage infiltration in the obstructed kidney, but this reduction has been observed only in short-term UUO, possibly because in late-stage UUO infiltration is dependent on cytokine formation that is independent of Ang II.…”
mentioning
confidence: 99%
“…ACE inhibitors reduce monocyte/ macrophage infiltration in the obstructed kidney, but this reduction has been observed only in short-term UUO, possibly because in late-stage UUO infiltration is dependent on cytokine formation that is independent of Ang II. 13 Before this strategy can be validated, the real impact, the effects of newer ROCK inhibitors and the optimal treatment combination for a specific renal or cardiovascular disease, related or unrelated to hypertension, need to be determined. Takeda et al's 12 new approach to prevention of renal and cardiovascular remodeling, using the combination of ROCK inhibition and RAS blockade, appears to be a promising therapeutic strategy.…”
mentioning
confidence: 99%